TC Protocol optimization: A quantitative approach. (September 2016) - Biondi, M.; La Penna, A.; Vanzi, E.; Mazzoni, L.N.; De Otto, G.; Belmonte, G.M.; Foderà, E.; Martini, R.; Imbriaco, G.; Carbone, F.S.; Guasti, A.; Volterrani, L.; et al.
Abstract : Introduction: Every year the number of performed CT scans is dramatically increasing, so that protocol optimization in terms of dose and image quality is mandatory. Purpose: To evaluate the efficacy of a novel objective method to compare different CT protocols based on a functional (F) encompassing signal to noise ratio (SNR), low contrast resolution (LCR) and CTDI. Materials and methods: Catphan 600 was scanned with a Discovery 750 (GE healthcare) 64 slices CT scanner varying tube voltage (kV = 100, 120, 140) and noise index (NI = 8, 12). Images were reconstructed using the standard FBP algorithm. LCR was assessed with CTP515 analysis, SNR was evaluated for every CTP404 insert And CTDI was recorded from consolle. An F value was calculated for each protocol as follows: F prot ( α ) = ( 1 - α ) ∑ w ins SNR ins prot SNR ins ‾ + LCR ‾ LCR prot + α CTDI ‾ CTDI prot where average values were computed over all the protocols used and α is weighting factor which was varied between 0 and 1 to differently balance dose and quality aspects. For each selected α higher F values are associated with a better trade-off between image quality and dose. Results: For α values between 0 and 0.6 higher F values were obtained for 120 kV/8 NI; for 0.7 ⩽ α ⩽ 1 the best trade-off was found for 100 kV/12 NI. Conclusion: The proposed CT protocol optimization approach provided an objective way to balance between dose and image quality in phantom. Further studies are in progress to assess the performances of the method in vivo. Disclosure: Authors disclose any relationship that may bias their presentation.